RESPONSIBILITAS GURU TERHADAP PRESTASI ANAK DIDIK DI SEKOLAH SMA NEGERI 3 LHOKSEUMAWE KELAS 12 PADA MATA PELAJARAN PAI (MATERI AKHLAKUL KARIMAH) - Rusna; Chaliddin (Postgraduate Program UIN Sultanah Nahrasiyah Lhokseumawe, 2025)
Teachers play an important role in determining the quality of learning and the success of students, especially in Islamic Religious Education (PAI) subjects. This article discusses how teacher responsibility affects the learning achievements of 12th grade students at SMA Negeri 3 Lhokseumawe in the subject of Akhlakul Karimah. Research shows that teachers' responsibilities in planning, implementing, evaluating, and setting an example have a positive influence on students' understanding of concepts and internalization of akhlakul karimah values. Based on the above theoretical framework, it can be concluded that teacher responsibility greatly influences learning success, both in terms of academics and character building. A responsible teacher will be able to provide effective learning, shape students' moral character, and improve their academic achievement. In teaching akhlakul karimah, it is important for teachers to be good role models, use appropriate methods, and create an environment that supports learning. Student achievement is not only measured in terms of test scores, but also in terms of the extent to which students are able to practice the values of akhlakul karimah in their daily lives.